Agronomic characteristics and productivity of corn silage in crop-livestock integration systems - Mattei, Eloisa; de Moraes Rego, Carlos Augusto Rocha; de Oliveira, Paulo Sérgio Rabello; Sampaio, Marinez Carpiski; Piano, Jeferson Tiago; Crusciol, Carlos Alexandre Costa [UNESP] (Centro Universitario de Maringa, 2024)
The consortium of maize with tropical forage grasses in crop-livestock integration (CLI) systems for silage aims to diversify production and improve soil quality. This study investigated the effect of monocropped maize or maize intercropped with tropical forage grasses, with and without nitrogen fertilization, on the agronomic characteristics and productivity of maize for silage. The experiment was conducted over two agricultural years in a randomized block design with four replications. The plots consisted of two species of forage grasses (Urochloa brizantha and Megathyrsus maximum) and monocropped maize as a control. Management practices of haymaking and grazing, as well as nitrogen fertilization, were evaluated. Evaluated characteristics included final stand, plant height, ear insertion height, stem diameter, and dry matter yield. In the first year, significant differences were observed in stem diameter and dry matter yield. In the second year, plant height and ear insertion height were also affected. The consortium with U. brizantha proved to be particularly beneficial, increasing dry matter yield by 4% in the first year and 34% in the second year compared to monocropped maize. Thus, the use of different grass species, management practices, and nitrogen fertilization resulted in better agronomic performance and higher dry matter yield of maize for silage.
Características agronômicas e a produtividade de milho silagem em área de integração lavoura-pecuária no Oeste do Paraná